Аналіз та перспективи використання CTF технології при виготовленні друкарських форм для основних способів друку - Одегова, Є. О. (ХНУРЕ, 2021)
In the modern market of printing services the tendency to increase the quality of printing is intensifying. There is an improvement in technologies that improve print quality. So digital technology has made significant strides, competing significantly with analog. But buying more technological equipment costs a lot of money, and xisting photocopiers will be more difficult to sell due to competition in the market and worn-out equipment.
Keywords: друкарська форма; друк